TOWARDS ENHANCING INTEROPERABILITY IN MEDICAL INFORMATION SYSTEM - ZAROUR, KARIM ZAROUR; ZAROUR, NACEREDDINE (Courrier du Savoir, 2014)
Medical  information  systems  evolve  constantly.  This  paper  shows  a  coherent  architectural  framework  that  allows  the development of interoperable medical information systems in measure or these systems evolve. This architecture is based on agent,  ontology  and  Peer  to  Peer.  The  proposed  architecture  is meant  to  include  all  the  concepts  necessary  to  perform  all activities related to medical information system. This work indicates how to attain the organizational interoperability.